2013
DOI: 10.1159/000351703
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Rutin on Oxonate-Induced Hyperuricemia and Renal Dysfunction in Mice

Abstract: Aims: The aim of the present study was to investigate the effects of rutin on potassium oxonate-induced hyperuricemia and renal dysfunction in mice. Methods: Rutin was administered orally 1 h after oxonate at doses of 25, 50 and 100 mg·kg-1. Serum uric acid levels and kidney function parameters were assayed. Mouse uromodulin levels in serum, urine and kidney were determined by the ELISA method. Simultaneously, the expression levels of renal organic ion transporters were detected. Results: Rutin sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 40 publications
2
17
0
2
Order By: Relevance
“…We identified chlorogenic acid, rutin, and kaempferol as marker compounds from the ethanolic extracts of C. tricuspidata leaves. Rutin is a flavonoid known to have various pharmacological activities, such as antioxidant, anti-convulsant, anti-inflammatory, anti-Alzheimer, and anti-hyperuricemia activities [ 27 , 28 , 29 , 30 ]. A previous study reported that rutin at doses of 50–100 mg/kg significantly reduced the levels of biomarkers such as serum urate, creatinine, blood urea nitrogen, and serum/kidney uromodulin in hyperuricemic mice [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified chlorogenic acid, rutin, and kaempferol as marker compounds from the ethanolic extracts of C. tricuspidata leaves. Rutin is a flavonoid known to have various pharmacological activities, such as antioxidant, anti-convulsant, anti-inflammatory, anti-Alzheimer, and anti-hyperuricemia activities [ 27 , 28 , 29 , 30 ]. A previous study reported that rutin at doses of 50–100 mg/kg significantly reduced the levels of biomarkers such as serum urate, creatinine, blood urea nitrogen, and serum/kidney uromodulin in hyperuricemic mice [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rutin is a flavonoid known to have various pharmacological activities, such as antioxidant, anti-convulsant, anti-inflammatory, anti-Alzheimer, and anti-hyperuricemia activities [ 27 , 28 , 29 , 30 ]. A previous study reported that rutin at doses of 50–100 mg/kg significantly reduced the levels of biomarkers such as serum urate, creatinine, blood urea nitrogen, and serum/kidney uromodulin in hyperuricemic mice [ 29 ]. In another study, rutin demonstrated dose-dependent hypouricemic effects by inhibiting xanthine dehydrogenase/xanthine oxidase (XDH/XO) activity [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another in vivo study has shown that the rutin application reduced detrimental effects and relative organ weight in mice, and more importantly, the increment of mean survival time was observed (Alonso-Castro et al, 2013). In vitro study demonstrated the altered Bax/Bcl2 ratio in cultured LAN-5 cell after the treatment of rutin (Chen et al, 2013). Moreover, rutin was known to induce cancer cell apoptosis along with proliferation, angiogenesis and/or metastasis inhibition in colorectal cell lines (Araújo et al, 2011).…”
Section: Anti-cancer Effectmentioning
confidence: 97%
“…Rutin exerted its hypouricemic action and renal function improvement by the regulation of renal organic ion transporters (Chen et al, 2013[ 3 ]).…”
Section: Dear Editormentioning
confidence: 99%